Thermal Induced Microstructures of KOH Etched Silicon Surface - Lamichhane, Shobha Kanta (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Anisotropic KOH etching of silicon for the fabrication of Micro-electro mechanical system (MEMS) part is based on surface finish and angular dependence of etch rate, creating thin diaphragm. The absolute values of orientation dependent etch rate is found to vary with thermal agitation. In this work, experimental results of etch rate is found quite consistent with simulated and are justify with their unusual values of activation energy along different planes. The various sites that an atom can occupy are not equivalent of their energy; some are more favorable to removal than others. In this paper attention is given to demonstrate thermal activation energy is the prime parameter that influences the behavior of etching mechanism as well as AFM surface morphology. Low-voltage contact mode atomic force microscopy (AFM) has been employed to analyze the morphology of the etched silicon surface at relevant different temperature. A systematic variation in morphological growth leads to stabilized surface structure under the influence of associated activation energy is concluded. Key words: Etching; Anisotropy; Etch rate; diaphragm; MEMS; LPCVD; SOI; AFM DOI: 10.3126/kuset.v5i1.2847 Kathmandu University Journal of Science, Engineering and Technology Vol.5, No.1, January 2009, pp 62-70